Commentary on Burns, Nembhard and Shortell, "Integrating network theory into the study of integrated healthcare": Revisiting and extending research on structural and processual factors affecting coordination. (July 2022) - Charns, Martin P.; Bolton, Rendelle E.
Abstract: Burns et al.'s innovative recommendation to use social network theory to study integration will contribute to our understanding of how healthcare systems can optimally deliver high quality, coordinated, person-centered care. We discuss three enhancements to this approach. (1) In increasing our attention to social network analysis and processual perspectives, we must not "throw out the baby with the bathwater" and abandon research that includes formal organizational structure. Structure remains an important focus for researchers and healthcare managers, who spend considerable resources on reorganizing. Since there is evidence that formal structure affects social processes and coordination, future research should build on that evidence and investigate how coordination is affected by the segmentation of organizations into units and the structures and processes designed to integrate interdependent work across those units. Conducting network analysis in the context of formal structure can help us better understand how formal structure affects both social networks and coordination. (2) Using multi-level, mixed methods, and qualitative research will be critically important to fully understand how and why formal organizational structure, social networks, and processual dynamics contribute to coordination or fragmentation of care. Because the relationships among these constructs occur not only within, but also across multiple levels, multi-level research is necessary to understand their effects on coordination. In considering the individual level, patients can be studied as a role embedded in networks. In addition, however, we must not lose a focus on patients as people at the center of multi-level networks, whose attitudes, values, preferences and goals may directly affect processual dynamics and coordination of care. (3) Finally, our field lacks precision in nomenclature, specification of levels, and the constructs within them, including ambiguity around even what is meant by "structure" and its variations. Furthermore, different authors use "macro", "meso", and "micro", differently, contributing to confusion in the discourse on organizational phenomena. Greater clarity and consistency in terminology is needed to facilitate research and improve communication across the field.